Assessment of Development Indices in Nigeria’s Bitumen Communities - Olatumile, Adekunle (Mediterranean Journal of Social Sciences, 2012)
Nigeria is well endowed with bitumen, with its potentials of wealth generation and prosperity. It becomes imperative to ensuresocio-economic development of the host communities in order to avoid a repeat of the crises that have characterized the Niger-Deltapetroleum enclave where the inhabitants felt needs are no met in the provision of infrastructure and social services. This study assessedthe inhabitants’ perception of the availability of development indices in the bitumen communities, such that a framework for the provisionof infrastructures along the needs of different communities can be developed. The sample was 1147 inhabitants. Data were collectedusing a questionnaire. ANOVA, MCA and Scheffe were used to analyse data. Findings showed variations in the indices of developmentand development needs of different communities. Infrastructures and social services should be provided according to the felt needs ofdifferent communities and local governments in the region.